Application of social media in supply chain 4.0 practices: a bibliometric analysis and research trends: Application of social media in supply chain 4.0 practices: a bibliometric analysis and research trends - Hoang, Thu-Hang; Nguyen, Nhi Pham Phuong; Hoang, Nhu-Y Ngoc; Akbari, Mohammadreza; Quang, Huy Truong; Binh, An Duong Thi (Operations management research, 2023)
In recent years, although scholars and practitioners in the supply chain (SC) field have become increasingly aware of the importance of social media for multipurpose applications, the subject remains unclarified about its functions and outcomes, especially in the 4.0 context. This review paper aims to visualize the big picture and structure of knowledge related to the application of social media in managing supply chains by adopting a bibliometric analysis on a sample of 354 research articles retrieved from the Web of Science during the period between 2008 and 2022 with two widely used bibliometric techniques: co-citation and co-word analysis. We discovered five major clusters of how social media is used in the supply chain context, including (1) in enhancing supply chain sustainability and business transformation, (2) social media analytics as an effective technique to extract business value, (3) in facilitating communication and coordination in the supply chain network, (4) in promoting social interaction and customer relationship management, and (5) in the development of supply chain relationship management. These will enable practitioners to adopt early changes in their SC, allowing them to become competitive and gain market leadership. Supply chain managers can connect with other SC stakeholders and share information through social media to improve operations, establish relationships, reduce risks, and altogether reach for sustainability. Potential research ideas are also offered for future investigation.